Jawabanmu

2014-05-04T00:24:56+07:00
Limit      Cos x - Sin(π/6)    =  Limit    Cos x - Cosπ/3
x⇒π/3      π/6  -  x/2              x⇒π/3     π/6 - x/2
                                          =  limit     -2Sin(1/2)(x + π/3)Sin(1/2)(x - π/3)
                                             x⇒π/3            π/6 - x/2
                                          =  limit      2Sin(x/2 + π/6)Sin(π/6 - x/2)
                                              x⇒π/3            (π/6 - x/2)
                                          = limit   2Sin(x/2 + π/6)
                                             x⇒π/3
                                          = 2Sin(π/6 + π/6)
                                          = 2Sin(π/3)
                                          = 2(1/2 √3)
                                          = √3